Adjuvant treatment with Xiaoqinglong formula for bronchial asthma: Protocol of systematic review and meta-analysis. Issue 35 (August 2019) - Wang, Long; Zheng, Xiuli; Hui, Yi; Wang, Baojia; Yang, Yu; Feng, Xianrong; Zhang, Tianyao; Ma, Li; Zhang, Xiaobo
Abstract: Background: Bronchial asthma is one of the most common chronic diseases in the world and has become a serious public health problem. Combination therapy has become the first choice for clinical treatment of bronchial asthma. In addition to the combined use of routine medication, traditional Chinese medicine as an adjuvant therapy is also considered. Xiaoqinglong Decoction (XQLD) is an effective prescription of traditional Chinese medicine in treating asthma, and there are more and more clinical reports about its combination with western medicine in treating asthma. Therefore, we designed this study protocol to evaluate the adjuvant role of XQLD in the treatment of bronchial asthma. Method: The following electronic databases will be systematically searched from inception to April 2019: PubMed, EMBASE database, Cochrane Library, China National Knowledge Infrastructure (CNKI), Wan Fang, Chinese Scientific Journals Database (VIP), and China Biology Medicine disc, (CBM). And the following primary outcomes will be tested, including effective rate (ER), pulmonary function (FEV1, PEF, FEV1/FVC), adverse reactions (AR). RevMan5 software will be used for literature quality evaluation and stata14.0 software will be used for data synthesis and analysis. Result: To evaluate the efficacy and safety of Xiaoqinglong decoction in combination therapy by observing the outcomes of efficacy, adverse reactions and pulmonary function. Conclusion: This study protocol will be used to evaluate the efficacy and safety of XQLD in combination with conventional drugs in the treatment of bronchial asthma, as well as the adjuvant role of XQLD in combination. PROSPERO registration number: CRD42019133549